Feasibility of thoracoscopic thymectomy for treatment of early‐stage thymoma. Issue 4 (11th June 2015) - Odaka, Makoto; Shibasaki, Takamasa; Asano, Hisatoshi; Marushima, Hideki; Yamashita, Makoto; Morikawa, Toshiaki
Abstract: Introduction: The objective of this study was to evaluate the feasibility of thoracoscopic thymectomy (TT) for treatment of early‐stage thymoma and to compare the outcomes with those after open thymectomy (OT). Methods: A retrospective review of 98 patients who underwent TT or OT of Masaoka stage I‐II thymoma without thymic cancer between 1996 and 2013 was performed. Results: Thoracoscopic thymectomy was performed in 67 patients, and OT was performed in 31 patients. The intraoperative blood loss amounts differed significantly between the TT group and OT group (100 vs 185 mL, P = 0.0070). The postoperative hospital stay was significantly shorter in the TT group than in the OT group (4 vs 12 days, P < 0.0001). No patient in the TT group underwent conversion to open surgery, and no surgical complications, such as massive bleeding, were observed. Two patients experienced recurrence in the TT group during the median postoperative follow‐up period of 65 months. No significant differences were found in the 5‐year disease‐free survival rates between the two groups. There were no significant differences in disease‐free survival as classified by Masaoka stage, World Health Organization type, and the extent of resection of the thymus. Conclusion: Our outcome showed that TT largely reduced the degree of invasiveness. The outcome was not inferior to that of OT. The results primarily demonstrated the feasibility of TT for treatment of early‐stage thymoma.